2022
DOI: 10.1002/adma.202204994
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Anti‐Inflammatory Supramolecular Nanofiber Hydrogel to Promote Anti‐VEGF Therapy in Age‐Related Macular Degeneration Treatment

Abstract: Age‐related macular degeneration (AMD) is a major cause of visual impairment and severe vision loss worldwide, while the currently available treatments are often unsatisfactory. Previous studies have demonstrated both inflammation and oxidative‐stress‐induced damage to the retinal pigment epithelium are involved in the pathogenesis of aberrant development of blood vessels in wet AMD (wet‐AMD). Although antivascular endothelial growth factor (VEGF) therapy (e.g., Ranibizumab) can impair the growth of new blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 43 publications
1
26
0
1
Order By: Relevance
“…S25). As expected, the heights of the a and b waves, which are closely associated with the activity of photoreceptor cells, RPE cells, retinal bipolar cells and Müller cells (31), were in the normal range, indicating that our AVB exhibited nearly no effect on the visual function of mice. In contrast, the two mice in the silicone oil group with abnormal eyes showed decreased visual function (a and b waves decreased).…”
Section: Evaluation Of Eyeball Structure and Retinal Functionsupporting
confidence: 77%
See 1 more Smart Citation
“…S25). As expected, the heights of the a and b waves, which are closely associated with the activity of photoreceptor cells, RPE cells, retinal bipolar cells and Müller cells (31), were in the normal range, indicating that our AVB exhibited nearly no effect on the visual function of mice. In contrast, the two mice in the silicone oil group with abnormal eyes showed decreased visual function (a and b waves decreased).…”
Section: Evaluation Of Eyeball Structure and Retinal Functionsupporting
confidence: 77%
“…Among them, immune checkpoint blockade using antibodies to block immune checkpoint pathways, such as the programmed cell death protein 1 pathway (PD-1/PD-L1), has been demonstrated to be an effective strategy in treating different types of cancers in the clinic (27). Considering the existence of complicated ocular structural barriers and low immunogenicity of the choroidal melanoma, intravenous administration of immune checkpoint antagonists is unable to achieve effective therapeutic benefit in previous researches (28), while intraocular injection of antagonists may cause many side effects, such as uveitis, endophthalmitis, and retinal detachment (29)(30)(31). Therefore, it is important to develop a biocompatible material that is able to serve as a vitreous substitute and drug reservoir simultaneously to preserve vision and sustainably release immunotherapeutic drugs to inhibit the recurrence of intraocular malignant tumors after surgical resection.…”
Section: Introductionmentioning
confidence: 99%
“…Chronological Remodeling of ITME by BetP@HA-gNCs. Based on previous studies, 51 it has been found that BetP can attenuate the inflammation-related nuclear factor κB (NF-κB) signaling pathway by interfering with the p65 translocation of NF-kB to the nucleus. It also suppresses the genetic transcription of proinflammatory cytokines and matrix metalloproteinase (MMP2) related transcription, thus reprogramming the tumor-promoting chronic inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…142 Especially in wet AMD, excessive VEGF production leads to the formation of abnormal, leaky blood vessels beneath the retina, resulting in damage and scarring that cause rapid vision loss. 143 Notably, Pegaptanib selectively binds to the VEGF165 isoform, the most biologically active form of VEGF in promoting angiogenesis. By binding to VEGF165, 142 Pegaptanib effectively blocks its interaction with the VEGF receptor on endothelial cell surfaces.…”
Section: Chemically Modified Platform Technology-enabled Clinical Usagementioning
confidence: 99%
“…Pegaptanib (Macugen) is the only antiangiogenic RNA aptamer designed to target VEGF in the treatment of AMD (Figure d), which is a progressive eye disorder that primarily affects the macula, the central part of the retina responsible for sharp and central vision and is a leading cause of vision loss in individuals aged 50 and older . Especially in wet AMD, excessive VEGF production leads to the formation of abnormal, leaky blood vessels beneath the retina, resulting in damage and scarring that cause rapid vision loss . Notably, Pegaptanib selectively binds to the VEGF165 isoform, the most biologically active form of VEGF in promoting angiogenesis.…”
Section: Current Status and Challenges Of Rna Therapeutics In Clinicsmentioning
confidence: 99%